485. A hypermutator strain of Pseudomonas aeruginosa in a COVID-19 patient with ventilator-associated pneumonia. (15th December 2022) - Nozick, Sophia; Ozer, Egon A; Medernach, Rachel; Mills, Jori; Wunderink, Richard; Hauser, Alan R
Abstract: Background: P. aeruginosa is a cause of hospital-acquired and ventilator-associated pneumonia. Hypermutator P. aeruginosa strains have been described in patients with cystic fibrosis and chronic respiratory infections but are rare in patients with acute P. aeruginosa infection. This case describes a hypermutator strain of P. aeruginosa found in a patient with COVID-19-associated acute respiratory distress syndrome (ARDS). Methods: Serial respiratory and blood cultures were collected. Short-read sequencing libraries were prepared using the Illumina Nextera XT kit, and whole-genome sequencing was performed using the Illumina NextSeq platform. Long-read sequencing libraries were prepared from unsheared genomic DNA using ligation sequencing kit SQK-LSK109 and sequenced on the Oxford MinION platform. Single nucleotide variants were identified by aligning reads from each isolate to the complete genome of the first available clinical isolate. Hypermutator assays were performed by measuring the mutation frequency rate for rifampin resistance. Antibiotic minimal inhibitory concentrations (MICs) were performed. Growth curves were performed with a starting OD600 of 0.1 with measurements taken every 30 minutes for 24 hours. Results: Seventeen respiratory and five blood isolates were obtained throughout 62 days of hospitalization. Fourteen of the 22 isolates exhibited hypermutator phenotypes by rifampin resistance assays, which demonstrated rapid accumulation of mutations. All five bloodstream isolates were hypermutators. MIC testing noted increased resistance to aminoglycosides, fluoroquinolones, and aztreonam in the hypermutator isolates. All bloodstream isolates descended from a single progenitor noted on whole-genome sequencing. Each hypermutator strain contained a mutation in the mismatch repair gene mutL, previously associated with the hypermutator phenotype. Genetic Tree of Patient Isolates The genetic tree highlights hypermutator versus non-hypermutator single nucleotide variants Conclusion: This case was notable for multiple isolates of hypermutator P. aeruginosa that persisted over weeks. The patient's COVID-19 infection and acute respiratory distress syndrome may have facilitated persistence of the P. aeruginosa lineage, allowing a hypermutator lineage to emerge. Disclosures: All Authors : No reported disclosures.